Influences of Tidal Flat and Thermal Discharge on Heat Dynamics in Xiangshan Bay - Kong, Gaoqiang; Li, Li; Guan, Weibing (Frontiers in Marine Science, 2022)
Water temperature in estuaries is sensitive to thermal discharges and large areas of tidal flats, and is an essential factor in maintaining the ecosystem in estuaries. Semi-enclosed water bodies with poor water exchange easily accumulates heat. This is especially in Xiangshan Bay with two power plants and a large area of tidal flats. This bay was used as an example to study the temperature and heat dynamics, considering the thermal discharge and tidal flat. A three-dimensional hydro-heat flux numerical model was developed and validated using field data of tidal elevation, currents, water temperature, and tidal flat temperature. The Finite Volume Community Ocean Model combines an accurate thermal discharge model with the air–water–tidal flat heat flux model. The findings show that thermal discharge provides heat to the bay in both summer and winter, and leads to an increase in water temperature of 0.73 °C in the entire bay in summer, while maintaining the temperature at 0.52 °C in winter. Atmosphere and open seas have greater impacts on the heat in the bay in both winter and summer. The atmosphere and tidal flats provide heat to the bay in summer and absorb heat from the bay during winter, while the open sea absorbs heat from the bay in summer and provides heat to the bay during winter. The effect of tidal flats in summer is less than that in winter, and provides 1.31 × 1013 J of heat to the bay in summer, while taking 8.63 × 1013 J of heat from the bay in winter. This study provides a deep understanding of the effects of tidal flats and thermal discharge on temperature and heat in macro-tidal bays and estuaries and would be applicable to similar bays worldwide.